2009
DOI: 10.1007/s11904-009-0019-7
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous meningitis in HIV-infected individuals

Abstract: HIV-infected individuals are at increased risk for all forms of extrapulmonary tuberculosis, including tuberculous meningitis. This risk is increased at more advanced levels of immunosuppression. The time interval between onset of symptoms and presentation to medical care may vary widely, and consequently individuals may present with acute or chronic meningitis. The clinical presentation of tuberculous meningitis in HIV-infected individuals is more likely to include an altered level of consciousness, cranial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
84
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 47 publications
4
84
1
3
Order By: Relevance
“…This is the first large prospective study using consecutively recruited unselected patients to evaluate the utility of a standardized quantitative T cell ELISPOT assay. The excellent performance outcomes of this assay likely represent a major advance in the rapid diagnosis of TBM, where diagnostic uncertainty often delays treatment, thus increasing mortality (8)(9)(10)(11). Preliminary reports suggest that that the ELISPOT assay may be a useful diagnostic tool (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first large prospective study using consecutively recruited unselected patients to evaluate the utility of a standardized quantitative T cell ELISPOT assay. The excellent performance outcomes of this assay likely represent a major advance in the rapid diagnosis of TBM, where diagnostic uncertainty often delays treatment, thus increasing mortality (8)(9)(10)(11). Preliminary reports suggest that that the ELISPOT assay may be a useful diagnostic tool (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Delaying therapy in patients with TBM, which frequently occurs because the diagnosis is often difficult to confirm, increases mortality (z30% despite treatment) (8)(9)(10)(11). Smear microscopy under high-burden programmatic conditions has a dismal yield (0-20%) (8,9,12,13).…”
mentioning
confidence: 99%
“…Although pulmonary TB is the most common presentation regardless of the stage of HIV infection, persons with advanced immune suppression are more likely to have extrapulmonary TB than are HIV-infected persons with relatively intact immunity or persons without HIV (15,33,83,136). Unlike persons without HIV, in whom extrapulmonary TB is usually found in the absence of pulmonary TB, HIVinfected persons with extrapulmonary TB are more likely to have concomitant pulmonary TB (15,212,229,255). Symptoms of extrapulmonary TB (with or without concomitant pulmonary TB) in a cohort of 199 HIV-infected patients included fever (95%), respiratory symptoms (66%), lymphadenopathy (62%), gastrointestinal symptoms (37%) with diarrhea and abdominal pain, and neurological symptoms (29%), including confusion and headache (229).…”
mentioning
confidence: 99%
“…Symptoms of extrapulmonary TB (with or without concomitant pulmonary TB) in a cohort of 199 HIV-infected patients included fever (95%), respiratory symptoms (66%), lymphadenopathy (62%), gastrointestinal symptoms (37%) with diarrhea and abdominal pain, and neurological symptoms (29%), including confusion and headache (229). Common sites of infection in extrapulmonary TB with HIV coinfection include the following (in decreasing order of frequency): disseminated TB involving bone marrow, blood, or liver; genitourinary TB; peripheral lymphadenitis; pleural TB; mediastinal TB with mediastinal lymphadenopathy and/or pericarditis; central nervous system (CNS) TB with meningitis or parenchymal infection with tuberculous abscesses and tuberculomas; mediastinal and pericardial TB (229); intra-abdominal lymphadenitis or peritonitis; musculoskeletal abscesses or osteomyelitis; or infection at other sites, including the adrenal glands and the gastrointestinal tract (15,33,229,255).…”
mentioning
confidence: 99%
“…These findings suggest reduced T1 response in HIV-infected patients, which contribute to their susceptibility to TB. 79,80 Clinical studies have shown the detrimental effects of TB on the course of HIV infection. M. tuberculosis probably increases HIV replication by inducing macrophages to produce tumor necrosis factor-, interleukin-1 and interleukin-6.…”
Section: Hiv and Tbmentioning
confidence: 99%